(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Introduction: Post partum psychiatric illness was initially conceptualized as a group of disorders specifically linked to pregnancy and childbirth and thus was considered diagnostically distinct from other types. More recent evidence suggest that Post partum psychiatric disorder is virtually indistinguishable from psychiatric disorders that occur at other times during a womans life. A wide variety of disorders are seen. Recognition of disorders for the mother-infant relationship is important, because these have pernicious long-term effects but generally respond to treatment. Objective: The objective of this review is to highlight the different type of psychiatric disorders in the puerperium and their management. Materials and Methods: Literature of reputed journals were used to prepare this article with the help of pshychiatric consultant. Results: Psychiatric disorder in puperium has got different severity. Commonly encountered disorders are: Maternity blues, Post natal depression, Post partum psychosis. Most common is related to manic depression, in which neuroleptic drugs should be used with caution. Eighty five (85%) of women experiences mood changes in postpartum. About 10%-15% of women develops post partum depression. 0.1% -0.2% experience postpartum psychosis. 4,00000 children are born to depressed mothers every year. Conclusion: The obstetrics team should alert both to possible interaction between psychological and obstretics factors and to the range of psychiatric disorders that may occur during pregnancy and puperium. The obstetrics and psychiatric teams should work together to improve their services locally and high light the need for greater service provision every where ic stress disorder, obsessions of child harm, and a range of anxiety disorders all require specific psychological treatments. Postpartum depression necessitates thorough exploration. Cessation of breastfeeding is not necessary, because most antidepressant drugs seem not to affect the infant. Controlled trials have shown the benefit of involving the childs father in therapy and of interventions promoting interaction between mother and infant. Owing to its complexity, multidisciplinary specialist teams have an important place in postpartum period. It should have clinical priority those are suffering from psychiatric problem during puperium as they are in crucial situation. It is important to recognize earliar to avoid undesirable consequences, which are harmful both for mother and infant.. According to severity patient may need counseling, social support, sometimes patient may need hospitalization in severe cases. There are several traditional methods worldwide sometimes they are beneficial and sometimes harmful to mother and infant. Bangladesh J Obstet Gynaecol, 2013; Vol. 28(1) : 38-43